2021
DOI: 10.1126/sciadv.abj5186
|View full text |Cite
|
Sign up to set email alerts
|

Novel synthetic pathway for the production of phosgene

Abstract: Chloride ions are efficient catalysts for the synthesis of phosgene from carbon monoxide and elemental chlorine at room temperature and atmospheric pressure. Control experiments rule out a radical mechanism and highlight the role of triethylmethylammonium trichloride, [NEt 3 Me][Cl 3 ], as active species. In the catalytic reaction, commercially available [NEt 3 Me]Cl reacts with Cl 2 to form [NEt 3 Me][Cl 3 ], enabling the insertion of CO into an activated Cl─Cl bond with a calculated energy barrier of 56.9 to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
0
20
0
7
Order By: Relevance
“…This makes them easy-to-handle chlorination reagents that have been used in numerous organic transformations . Very recently, we found that [NEt 3 Me]­[Cl 3 ] can directly react with CO, without further activation by light or heat, to form phosgene (COCl 2 ), a major intermediate in the synthesis of polyurethanes and polycarbonates . Additionally, trichloride ionic liquids are useful for the oxidative dissolution of metals and alloys for metal recycling applications, as demonstrated by the group of Binnemans and others. …”
Section: Introductionmentioning
confidence: 99%
“…This makes them easy-to-handle chlorination reagents that have been used in numerous organic transformations . Very recently, we found that [NEt 3 Me]­[Cl 3 ] can directly react with CO, without further activation by light or heat, to form phosgene (COCl 2 ), a major intermediate in the synthesis of polyurethanes and polycarbonates . Additionally, trichloride ionic liquids are useful for the oxidative dissolution of metals and alloys for metal recycling applications, as demonstrated by the group of Binnemans and others. …”
Section: Introductionmentioning
confidence: 99%
“…On one hand, there is an increasing request to understand industrial processes at the molecular level in order to use this information for the further process development. Many theoretical investigations are going on in the field of urethane industry, including phosgene production in presence of [NEt 3 Me]Cl/[NEt 3 Me][Cl 3 ] catalyst system [ 16 ], thermal decomposition of phosgene [ 17 ], the formation of other diamine intermediate (MDA), the phosgenation of MDA [ 15 ], the liquid structure of different isocyanates [ 18 , 19 ], urethane formation with an excess of isocyanate or alcohol [ 20 ], and in presence of catalysts [ 21 ], just to name a few. On the other hand, the chemical industries largely use the phosgenation of 2,4-TDA.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, we found that [NEt 3 Me][Cl 3 ] is also a useful chlorinating agent reacting with carbon monoxide to the base chemical phosgene (COCl 2 ). Interestingly, our studies indicate that the trichloride anion in [NEt 3 Me][Cl 3 ] has a Cl−Cl bond which is much weaker than in elemental chlorine facilitating the insertion of carbon monoxide into the Cl−Cl bond of the trichloride [3] …”
Section: Figurementioning
confidence: 89%
“…Interestingly, our studies indicate that the trichloride anion in [NEt 3 Me][Cl 3 ] has a ClÀ Cl bond which is much weaker than in elemental chlorine facilitating the insertion of carbon monoxide into the ClÀ Cl bond of the trichloride. [3] In contrast to elemental chlorine, [NEt 3 Me][Cl 3 ] contains the chemically inert cation [NEt 3 Me] + which has proven to be very useful to stabilize various reactive anions. [4] Therefore, we speculated that the exceptional ability of [NEt 3 Me][Cl 3 ] to serve both as a strong chlorination reagent and to form stable salts with unique anions would enable the preparation of unknown chlorine-containing compounds.…”
mentioning
confidence: 99%